Critical Success Factors in New Product Development: A Survey in Malaysian Manufacturing Industry - Mohd Rohaizad, Abdul Latib (2011)
The importance of new product development (NPD) has grown radically over the last few decades, and is now the leading driver of competition in many industries all over the world including Malaysia. This study only focuses on critical factors as key success in NPD for manufacturing sector that has been the engine of the growth of the Malaysian economy for the past 30 decades. There are many critical factors that contribute successful in developing new products. Examples of such critical success factors are top management support, external support, NPD strategies, and NPD teams. This study examined the relationship between top management support, external support, NPD strategies and NPD teams on NPD success. A total of 122 respondents in various companies within the manufacturing industry in Northern Peninsular Malaysia participated in this study by completing the survey questionnaire. From this study of critical factors, the results found that the variables show the significant relationship on NPD success by the respondents of Malaysian manufacturing sector.